2015
DOI: 10.1021/acs.jced.5b00268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Poly(lactic acid) on the Solubility of CO2, N2, and He Gases in Dichloromethane

Abstract: The effect of dissolved poly­(lactic acid) (PLA) on the solubility of gases (CO2, N2, and He) in dichloromethane (CH2Cl2) was investigated, between 288 and 303 K, by measuring the equilibrium pressure in a closed vessel containing a gas and CH2Cl2 solutions of different types (molecular weights) and concentrations of PLA. The results show that, in the absence of PLA, the order of the solubility of gases in dichloromethane was He < N2 < CO2. Furthermore, an increase in the concentration of PLA did not appreciab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Here, it is assumed that the radius of a volatile liquid droplet R 1 is 1.0 mm, the number of bubbles q is 3.0 × 10 8 , and S = 5.45 × 10 –4 . The parameters of p 1 * and A are given as a function of temperature. , These calculation results indicate that there is a stable solution of the equilibrium bubble radius at 313.15 and 318.15 K, but no stable solution exists at 323.15 K. It should be noted that the saturation vapor pressure of dichloromethane at 313.15 K is approximately 1 atm, which suggests that even if the saturation vapor pressure of a volatile liquid is higher than 1 atm, that is, p 1 * > 1, noncondensable gas bubbles still have a stable equilibrium radius in a closed system. Furthermore, it is also determined that if p 20 * increases from 1.0 to 1.5, that is, if the total number of moles of a noncondensable gas in the system increases, a stable equilibrium radius appears at a lower temperature.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Here, it is assumed that the radius of a volatile liquid droplet R 1 is 1.0 mm, the number of bubbles q is 3.0 × 10 8 , and S = 5.45 × 10 –4 . The parameters of p 1 * and A are given as a function of temperature. , These calculation results indicate that there is a stable solution of the equilibrium bubble radius at 313.15 and 318.15 K, but no stable solution exists at 323.15 K. It should be noted that the saturation vapor pressure of dichloromethane at 313.15 K is approximately 1 atm, which suggests that even if the saturation vapor pressure of a volatile liquid is higher than 1 atm, that is, p 1 * > 1, noncondensable gas bubbles still have a stable equilibrium radius in a closed system. Furthermore, it is also determined that if p 20 * increases from 1.0 to 1.5, that is, if the total number of moles of a noncondensable gas in the system increases, a stable equilibrium radius appears at a lower temperature.…”
Section: Resultsmentioning
confidence: 86%
“…For example, it is difficult to control the total amount of dissolved air in a liquid droplet (a dichloromethane solution of PLA). Regarding this point, we discovered that the solubility of CO 2 , N 2 , and He gases in a dichloromethane solution of PLA depends on the concentration of the dissolved polymer of PLA. , Another difficulty is associated with the process of enhancing the coalescence of nucleated microbubbles and the formation of a large single bubble inside the liquid droplet. Regarding this point, we found that many multi-void microcapsules have been produced under certain conditions .…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that p 1 ″ is close to the saturation vapor pressure of pure CH 2 Cl 2 at low c PLA and the air pressure inside the bubbles is approximately equal to the liquid pressure. The value of r b was predicted to be 0.95 µm at low c PLA and 298 K. Except for low c PLA conditions, because the partial vapor pressure varies with its mole fraction in solution, p 1 ″ should decrease with increasing c PLA (Molino Cornejo et al, 2016). However, analysis of the data of microbubbles nucleated with and without ultrasound revealed that there was no statistical difference among the measurements with a Cronbach´s alpha of 0.92; which implies that the size of the bubble is not affected by the presence of the ultrasound when compared to the diffusion only driven process.…”
Section: Equilibrium Bubble Radiusmentioning
confidence: 98%
“…However, at the first contact with the aqueous continuous phase, the hydrophobic sections of the polymer (PLA) reduce their size in order to minimize the surface area in contact with the continuous phase, thus avoiding any inclusion of H 2 O. In addition, since the enclosed gas is a mixture of CH 2 Cl 2 and air (the volume ratio of air to CH 2 Cl 2 is 0.13 (Molino Cornejo et al, 2016), more CH 2 Cl 2 gas diffuses into the adjacent continuous aqueous phase. The fact that the capsule shrinks is also credited with the diffusion of CH 2 Cl 2 gas into the aqueous phase.…”
Section: Equilibrium Bubble Radiusmentioning
confidence: 99%